Building library 3.0 : issues in creating a culture of participation - Evans, Woody (Oxford : Chandos Pub., 2009)
This book is for information professionals and librarians who want to reach out to their users with the tools of Web 2.0 wisely.
Library 2.0 : the fundamentals -- New library users -- Folksonomic exchanges : authority of the people -- Social networking : making it work -- Mobile life and QR code -- Second Life and other massively multi-user environments -- Arphids [RFIDs] : promise and dangers -- Fundamentally good service -- Conclusion : no more walls.
Includes bibliographical references (p. 179-184) and index.
rua 06/06/13
Loans
Keywords: Libraries -- Effect of technological innovations on; Libraries and the Internet; Library administration; Public services (Libraries); Communication in library science -- Technological innovations; Web 2.0.; Bibliothek; Semantic Web; Elektronische Bibliothek